EXPERIMENTAL MODELS FOR HEPATOTOXICITY - Singh, Gurfateh; Dhadwal, Nancy; Harikumar, S.l. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The liver is among the most complex and important organs in the human body. Hepatotoxicity is a leading cause of morbidity and mortality, and its prevalence is continuously increasing day by day in the industrialized nations. Hepatotoxicity is characterized by nuclear pyknosis and eosinophilic cytoplasm, followed by large excessive hepatic lesion, fatty changes, lipid peroxidation leads to hepatic centrilobular necrosis. Paracetamol, antiâ€‘tubercular drugs, alcohol, and azathioprine are considered to be the major risk factors implicated in the progression of hepatotoxicity. Various signaling mechanisms, such as activation of innate immune system like Kupffer cells, natural killer (NK) cells, and NKT, inflammatory mediators, intracellular Ca2+ concentration and reactive oxygen species are involved in the pathogenesis of hepatotoxicity. At present, there is no promising therapy is available to treat patients with hepatotoxicity due to lack of understanding of signaling culprits involved in the pathogenesis of hepatotoxicity. Animal models are being developed to better understand the disease pathogenesis and develop drugs for hepatotoxicity. In the present review, we have discussed various experimental models for hepatotoxicity, which may open vistas for developing new drugs to treat hepatotoxicity. Keywords: Hepatotoxicity, Carbon tetrachloride, Serum glutamic oxalacetic transaminase, Natural killer T, etc. Â